Weed management practices in rice (Oryza sativa) + brahmi (Bacopa monnieri) intercropping system - JOSHI, NEESHU; PANDEY, SUNITA T; KUMAR, AJIT; SINGH, V PRATAP; GAUTAM, POONAM (The Indian Journal of Agricultural Sciences, 2019)
A field study was carried out during two consecutive kharif seasons 2015–2016 at Norman E Borlaug Crop Research Centre, G B Pant University of Agriculture and Technology, Pantnagar, Uttarakhand, to evaluate the effect of different weed management practices and different row ratios on yield, yield attributes and economics of the rice (Oryza sativa L.) + brahmi (Bacopa monnieri) intercropping system. The dominant weed floras were Echinochloa crus-galli, Echinochloa colona, Alternanthera sessilis, Caesulia axillaris and Cyperus rotundus. Among different herbicides, pendimethalin followed by (fb) cyhalofop-butyl fb, one hand weeding at 45 days after sowing in 2:1 row ratios had minimum weed density (16.83 and 9.82/m2), dry weight (7.35 and 3.97 g/m2) and highest weed control efficiency (73.36 and 83.45%). Intercropping of rice with brahmi, exhibited greater potentiality and realized significantly higher plant height, dry matter accumulation, number of nodes, number of branches, number of panicles/m2 and 1000 grain weight. Dry herbage yield of brahmi and grain yield were highest in sole crop of rice (5.3 and 6.56 t/ha) and brahmi (2.07 and 2.35 t/ha). Furthermore, pendimethalin fb cyhalofop-butyl fb one hand weeding at 45 DAS in 1:1 ratio of rice and brahmi gave highest net returns (255426.1 and 317163.1/ha) and benefit cost ratio (10.1 and 11.07) and also high value of land equivalent ratio (1.76 and 1.85) and area time equivalent ratio (0.88 and 0.92) during both years.